On optimizing the number of repetition in an operation skill training program based on cost of quality and learning curve. Issue 1 (1st January 2019) - Prasetyo, Hoedi; Rosyidi, Cucuk Nur; Pujiyanto, Eko
Abstract: An operation skill training is useful to enhance the skill of the workers in a shop floor. The number of repetition is a prominent factor in the training and has to be determined in such a way so that the training can be performed cost-effectively. In this research, a novel model is developed to determine the optimal number of repetition in an operation skill training program by integrating learning curves into cost of quality. A real case study in a twist drill manual-sharpening training program is given to show the implementation of the model. A sensitivity analysis is performed to show the effect of the model's parameters to the decision variable and the objective function. Based on the optimization result, the optimal number of repetitions in the case study is found to be 26. It is also found that the developed model can be used to estimate the training cost, and to determine the training's target.